2022
DOI: 10.1039/d2nj04463c
|View full text |Cite
|
Sign up to set email alerts
|

First 1-hydroxy-1H-imidazole-based ESIPT emitter with an O–H⋯O intramolecular hydrogen bond: ESIPT-triggered TICT and speciation in solution

Abstract: Search for new types of ESIPT-capable molecules is crucial for understanding factors controlling the ESIPT photoreaction. In this paper we present combined experimental and theoretical studies of the proton transfer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 140 publications
0
6
0
Order By: Relevance
“…A non-constrained geometry optimization of the S 1 state directly leads to a non-planar geometry near the conical intersection (CI) between the S 0 and S 1 states ( Figure 9 b). According to the literature, ESIPT is often coupled with the radiationless deactivation via twisted intramolecular charge transfer (TICT) states of a non-planar biradicaloid nature [ 83 , 85 , 94 , 95 , 96 , 97 , 98 , 99 ]. This non-planarity arises from the twisting around a double-like bond between proton-donating and proton-accepting moieties (around the C Ph –C Imid bond in our case).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A non-constrained geometry optimization of the S 1 state directly leads to a non-planar geometry near the conical intersection (CI) between the S 0 and S 1 states ( Figure 9 b). According to the literature, ESIPT is often coupled with the radiationless deactivation via twisted intramolecular charge transfer (TICT) states of a non-planar biradicaloid nature [ 83 , 85 , 94 , 95 , 96 , 97 , 98 , 99 ]. This non-planarity arises from the twisting around a double-like bond between proton-donating and proton-accepting moieties (around the C Ph –C Imid bond in our case).…”
Section: Resultsmentioning
confidence: 99%
“…The quantum chemical calculations presented in this study were conducted using density functional theory (DFT), time-dependent DFT (TDDFT) and Tamm–Dancoff approximated DFT (TDADFT) methods in Gaussian 16 software package [ 103 ]. We used the hybrid exchange-correlation functional PBE0 [ 104 ] since our previous studies demonstrated its satisfying performance in modeling photophysical and photochemical properties of organic ESIPT-emitters [ 83 , 85 ]. Compared with probably the best known hybrid functional B3LYP, PBE0 provides absorption energies that are closer to the experimental data, while B3LYP tends to red-shift some vertical absorptions for L H,OH and L OH,OH ( Supplementary Materials , Figures S12 and S13 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emission of ESIPT-capable dyes is highly sensitive to solvents, 43–50 substitution in the ESIPT-dye core, 51–71 protonation/deprotonation, 72–80 and coordination of metal ions. 81–96 Normally, the latter process is coupled with the deprotonation of ESIPT-dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40][41] This plethora of emissive excited states makes ESIPT-capable compounds an appealing platform for the design of multicolor luminescent materials. 42 The emission of ESIPT-capable dyes is highly sensitive to solvents, [43][44][45][46][47][48][49][50] substitution in the ESIPT-dye core, protonation/deprotonation, [72][73][74][75][76][77][78][79][80] and coordination of metal ions. [81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Normally, the latter process is coupled with the deprotonation of ESIPT-dyes.…”
Section: Introductionmentioning
confidence: 99%